THE EFFECT OF FINANCIAL LITERACY ON MSME FINANCIAL MANAGEMENT IN TANJUNGSARI DISTRICT, SUMEDANG REGENCY - Beureukat Beureukat; Irma Setyawati (Jurnal Ekonomi, 2023)
The realization of effective management, accountable financial management, and genuine added value is the key to success for micro, small, and medium-sized enterprises (MSMEs) while competing in worldwide marketplaces. This is especially true in light of the period of globalization. Literacy in financial matters is absolutely required for actors in MSME businesses in order to manage their companies' finances. This study aims to inquire into and evaluate the effect that financial literacy has on the management of MSME's (small and medium-sized companies) finances in the Tanjungsari District. Both quantitative and descriptive methods were used to achieve the study's goals. The research showed that MSME in the Tanjungsari Sumedang District benefited from increased financial literacy, and that this benefit amounted to 18.2% better financial management overall.